2021
DOI: 10.3390/ijms22168796
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating DNA Replication and Mitosis through Ubiquitin/SUMO and CDK1

Abstract: Post-translational modification of the DNA replication machinery by ubiquitin and SUMO plays key roles in the faithful duplication of the genetic information. Among other functions, ubiquitination and SUMOylation serve as signals for the extraction of factors from chromatin by the AAA ATPase VCP. In addition to the regulation of DNA replication initiation and elongation, we now know that ubiquitination mediates the disassembly of the replisome after DNA replication termination, a process that is essential to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 141 publications
0
11
0
Order By: Relevance
“…Post-translational modification of the DNA replication machinery by ubiquitin and small ubiquitin-like modifier (SUMO) plays key roles in cell division, DNA replication/repair, signal transduction, and cellular metabolism (184). Recent research revealed that ubiquitin/SUMO pathways are essential regulators of DNA replication during initiation, the S phase or elongation, and DNA replication termination (185). SUMO/ubiquitin equilibrium at active DNA replication forks controls CDK1 activation.…”
Section: Ubiquitin and Sumomentioning
confidence: 99%
“…Post-translational modification of the DNA replication machinery by ubiquitin and small ubiquitin-like modifier (SUMO) plays key roles in cell division, DNA replication/repair, signal transduction, and cellular metabolism (184). Recent research revealed that ubiquitin/SUMO pathways are essential regulators of DNA replication during initiation, the S phase or elongation, and DNA replication termination (185). SUMO/ubiquitin equilibrium at active DNA replication forks controls CDK1 activation.…”
Section: Ubiquitin and Sumomentioning
confidence: 99%
“…CHK1 phosphorylation upon VCPi leads to the activation of the checkpoint and the arrest of the cell cycle in G2/M. Since VCP/p97 unloads the replisome upon DNA replication termination 63 , it has been previously proposed that the G2/M arrest induced by VCPi is related to the accumulation of replication proteins on chromatin 47 . A recent study has shown that replisome disassembly in S phase is necessary to recycle DNA replication factors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the control of POLA/PRIM accumulation on chromatin after origin firing, our data puts forward a role for VCP/p97 in the control of DNA replication fork progression. VCP/p97 participates in different steps of DNA replication: it extracts CDT1 during DNA replication initiation 20,21 , maintains the ubiquitin/SUMO equilibrium during the elongation phase 16,63,72 , and removes the replisome from chromatin upon DNA replication termination 63,73 . We show that VCP/p97 activity is necessary to sustain a physiological fork rate in a POLA/PRIM dependent manner, and this effect could be mediated by several mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…VCP has several roles in DNA replication as a major mediator of the ubiquitin and SUMO systems [ 132 ]. To initiate DNA replication, the many origins of DNA replication must be prepared and evenly distributed before the cell can transition from the G1 to the S-phase, termed origin licensing [ 128 ].…”
Section: Roles Of Vcp In the Nucleusmentioning
confidence: 99%